2017
DOI: 10.1002/ccd.27387
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses to larger volume intra‐aortic balloon counterpulsation: Hemodynamic and clinical outcomes

Abstract: ObjectivesExamine hemodynamic and clinical correlates of use of an intra‐aortic balloon pump catheter in a single center.BackgroundThe intra‐aortic balloon pump catheter (IABC) has been used for 50 years but the clinical benefit is still debated. We reviewed 76 patients with right heart catheter measurements prior to IABC to assess response and outcomes.MethodsAll patients who received IABC with a 50cc balloon for at least 1 hour were included in this retrospective chart review study. Demographics, comorbiditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…Since IABP clinical benefit is still debated and also there is a controversy between the findings of different studies, physicians, cardiologists, and surgeon should be knowledgeable about the possible factors that interrupt IABC efficacy and this information should be considered in IABP hemodynamic evaluation. [77] As a general rule, the application of IABC in the era of interventional revascularization is highly recommended by many cardiologists and cardiac specialists at high-risk patients. In conclusion, IABP support should be still applied after cardiac surgery in high-risk cohort of patients with postcardiotomy low output syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Since IABP clinical benefit is still debated and also there is a controversy between the findings of different studies, physicians, cardiologists, and surgeon should be knowledgeable about the possible factors that interrupt IABC efficacy and this information should be considered in IABP hemodynamic evaluation. [77] As a general rule, the application of IABC in the era of interventional revascularization is highly recommended by many cardiologists and cardiac specialists at high-risk patients. In conclusion, IABP support should be still applied after cardiac surgery in high-risk cohort of patients with postcardiotomy low output syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The hemodynamic effects of an IABP stand out better with larger balloon size. Several recent studies demonstrate that the use of larger 50-cc balloons resulted in a greater reduction in cardiac filling pressures and increased CO compared with the 40-cc IABPs [ 44 – 46 ]. Unfortunately, 50-cc IABPs were generally not used in the major landmark studies so far, since the 50-cc IABP was only introduced in 2012.…”
Section: Discussionmentioning
confidence: 99%
“…In 60/75 patients who underwent right heart catheterization in the before-mentioned cohort of Visveswaran, CO and cardiac index increased up to 7 L/min and 3.4 L/min/m 2 respectively, while in the remaining 20% non-responders CO decreased. Remarkably, the mortality rate between responders and non-responders was equal [ 46 ]. In Hsu’s study, all patients showed an initial improvement in CO within the first 24 h, but in patients with adverse events, CO declined after 24–48 h post IABP implantation [ 26 •].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The larger-capacity 50 cm 3 IABP provides greater diastolic augmentation and systolic unloading. [8][9][10] Although the femoral artery is commonly used for access, the positive safety profile and feasibility of transthoracic IABPs has been reported by several investigators. 11,12 IABPs can be placed surgically by attaching a Gore-Tex graft to the subclavian or axillary artery.…”
Section: Intra-aortic Balloon Pumpmentioning
confidence: 99%